Upaya Meningkatkan Kemampuan Berhitung Melalui Metode Bermain Kartu Angka pada kelas Venus KB Budi Mulia Al Bayaan - Mufidah, Asna; Hidayah, choirul (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
This classroom action research aims to (1) describe efforts to develop children's numeracy skills through the method of playing number cards (2) describe improving the learning process in children's numeracy skills through the method of playing number cards. The subjects in this research were students from the Venus KB Budi Mulia Al Bayaan group for the 2022/2023 academic year. This research is collaborative between researchers and class teachers. The data is used to determine the increase in children's numeracy skills and to understand the learning process through number card games through observation and field notes. The data analysis technique uses descriptive qualitative with interactive analysis based on the results of observations of learning activities and the results of actions that have been taken. The results of this research show that there is a significant increase in children's numeracy skills in the learning process using the number card method. Based on this, it can be seen from the child's abilities which include two indicators, namely counting number cards and counting number cards 1 -10. Before the action was carried out, the child's numeracy ability value was 13%, after the action in cycle I was carried out it increased to 75%, and at the end of the action in cycle II it increased to 95%. This research concludes that the application of the number card method in learning at the Budi Mulia Al Bayaan KB can improve children's numeracy skills.